OP I – 1 Ambient air pollution and depressive symptoms in elderly women: results from the salia study. (18th March 2018) - Altug, Hicran; Hüls, Anke; Fuks, Kateryna; Suguri, Dorothee; Krämer, Ursula; Schikowski, Tamara
Abstract : Background/aim: Numerous epidemiological studies have shown effects of long-term exposure to air pollution on cardiovascular, respiratory and cognitive health. However, studies investigating the effects of air pollution on depressive symptoms are limited and results are conflicting. We aimed to examine the association between long-term exposure to ambient air pollution and depressive symptoms in elderly women. Methods: Our analyses were based on 821 women (age ≥65 years) living in the Ruhr area and Southern Münsterland, Germany (SALIA cohort, follow-up examination, 2008–2009). Annual average concentrations of particulate matter (PM) size fractions and nitrogen oxides (NO x ) were assigned to home addresses by land-use regression (LUR) models. Self-reported depressive symptoms were evaluated using the Centre for Epidemiological Studies – Depression Scale (CES-D) and a CES-D score ≥16 as a dichotomous outcome was used in analyses. Our adjusted logistic regression models included age, body mass index, smoking status, environmental tobacco exposure at home, educational status, urban/rural living, physical activity, cardiovascular disease, respiratory diseases and diabetes as covariates. Results: A total of 129 women (15.7% of the individuals) had a CES-D score ≥16. We observed significant positive associations between an interquartile range (IQR) increase of PM10 (OR=1.294; 95% CI: 1.022 to 1.640), PM2.5 (OR=1.594; 95% CI: 1.120 to 2.270), NO2 (OR=1.418; 95% CI: 1.044 to 1.924) and NO x (OR=1.507; 95% CI: 1.108 to 2.051) with the presence of depressive symptoms. No significant associations were observed for an IQR increase of absorbance of PM2.5, coarse fraction of PM and traffic indicators (traffic load and residential proximity). Conclusion: In this study, mean annual concentrations of PM10, PM2.5, NO2 and NOx were positively associated with depressive symptoms in elderly women. Findings of our study suggest that air pollution is not only a risk factor for physical health but might also have adverse effects on mental health among elderly women.